Strategie przekładu Adama Pomorskiego na przykładzie tłumaczenia wiersza Метель Borysa Pasternaka - Plakueva-Olejniczak, Marianna (Acta Polono-Ruthenica, 2018)
The subject of this article’s research is the problem of translation of poetic texts on the basis of a poem Метель by Boris Pasternak. The work aims to analyse certain mechanisms and processes involved in the translation of poetic texts which are not limited to the rhythmical layer but also include lexical and phonological dimension. The article examines strategies of translation created by Adam Pomorski, a critic, essayist and recognised translator of Russian, German and English belles-letters, and a chairman of the Polish PEN Club. Pomorski reckons that translation is a “reconstruction of the prototype” within the norms and conventions, while all rest is a result of individual style. While creating literature, some artists recall the sounds that they associate with the literary pictures. This way, the language goes beyond the sematic layer of a work, while trying to imitate the sounds through onomatopoeic words, acoustic expressions and also other ways that influence the rhythmisation of a poem and bring out the connotation to the musical side of things. We will try to investigate how the poetic word of a prototype changed upon a translation on the basis of a Метель poem Pasternak.